“Everything I need is within me” : Pre-service teachers’ self-efficacy beliefs in Transnational teacher education programme - Haukilahti, Maria (My University, 2022)
Teachers are the professionals that assist others to acquire knowledge and before reaching the required amount of vocational knowhow to do so, they must be trained. Different transnational education projects bring students to attain university degrees beyond the borders and educational policies of their country. This thesis presents a glimpse of the process of becoming a teacher in European context, in a transnational teacher training programme tailored for a Sub-Saharan African client. Scholars have been interested in pre-service teachers’ professional development for they face the same challenges as in-service teachers right from the onset of their careers. Their problem-solving skills and critical thinking are contested together with the command of instructional strategies, classroom management, and student engagement. Sound teacher’s self-efficacy beliefs (TSE) indicate successful implementation of the above-mentioned skills, which is why this approach has become rather popular when studying pre-service teachers. Mixed method approach was used to encompass the studied phenomenon as thoroughly as possible when the sample remained small. The Ohio States Teacher Efficacy Scale (OSTES) questionnaire was used to collect the quantitative data which also served as the base for questions for focus group interview. A combination of statistical analysis and grounded theory was adopted to find out the pre-service teachers’ level of TSE, what are the factors impacting it, and how the level of TSE could be enhanced if needed. The results indicated generally relatively strong self-efficacy beliefs among the studied pre-service teachers. The factors impacting their TSE seem to be connected to their lack of teaching experience and vocational knowledge, realities in their home country, and their individual differences in character. Both pre-service teachers and teacher educators indicated in their interviews that possibilities to enhance TSE in a transnational education programme not only adding elements to the study programme, but also preparing teacher educators for a group of students that represent different culture.
Keywords: transnational education, teacher education, teacher’s self-efficacy